Temporal phase and amplitude statistics in coherent radiation - Wright, Dean (2005)
Interest in coherent remote sensing systems has stimulated investigations in the properties laser propagation through extended atmospheric turbulence. This thesis investigates the statistics of phase, and phase related, observables using analytical and computational techniques, together with experimental results.